The Effect of Clopidogrel and Ticagrelor on Human Adipose Mesenchymal Stem Cell Osteogenic Differentiation Potential: In Vitro Comparative Study - Sally S. Mohamed; Hala F. Zaki; Shereen N. Raafat (Advances in Pharmacological and Pharmaceutical Sciences)
Ticagrelor (TICA) and clopidogrel (CLP) are extensively used antiplatelet drugs that act by antagonizing the P2Y12 receptors that are found on platelets in addition to bone cells. Aim. The purpose of this study was to investigate the effect of clopidogrel and ticagrelor on stem cells osteogenic differentiation in vitro. Methods. Human adipose-derived mesenchymal stem cells (hAd-MSCs) were divided into (1) control group, (2) osteogenic group (osteo group), (3) clopidogrel group (CLP group), and (4) ticagrelor group (TICA group). The osteogenic differentiation potential was determined by mineralization nodule formation using Alizarin Red S staining, measuring ALP enzyme activity by alkaline phosphatase assay. Quantitative determination for osteogenic markers included osteocalcin (OC); runt-related transcription factor 2 (RUNX2) performed using western blot; osteoprotegerin (OPG) using enzyme-linked immunosorbent assay (ELISA) and inflammatory markers; and tumor necrosis factor (TNF-α) and interleukin-6 (IL-6) measured using real-time polymerase chain reaction quantitative (RT-PCR) and ELISA. Results. In comparison to all study groups, the TICA group showed significant increase in the mineralized extracellular matrix, ALP enzyme activity, and bone markers expression as RUNX2 (P<0.0001), OC, and OPG (P<0.05). The expression of IL-6 and TNF-α was determined by RT-qPCR and ELISA techniques. TICA and CLP significantly decreased both markers compared to the control group. The TICA group showed statistically significant lower levels of both markers (P<0.0001) than the CLP and control groups via the ELISA technique. Conclusion. TICA may possess a positive effect on hAd-MSCs osteogenic differentiation compared to CLP.